1995
DOI: 10.1021/la00004a032
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Uniaxial Molecular Orientation in Langmuir-Blodgett Films by Infrared Reflection Spectroscopy

Abstract: In analyzing optical properties of multilayered LB films with the uniaxial anisotropy around the surface normal, a new method for calculating infrared reflection-absorbances was developed, by extending Drude's anisotropic calculation theory for two-phase system to Hansen's optical theory for thin isotropic multilayers. With this method, infrared external reflection spectra of a 9-monolayer LB film of cadmium stearate prepared on a gallium arsenide substrate were analyzed to obtain molecular orientations. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
206
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(216 citation statements)
references
References 20 publications
10
206
0
Order By: Relevance
“…IR ER measurements 8,9,12 were performed on a Thermo Fischer Scientific (Madison, WI) Magna550 FT-IR spectrometer equipped with a Harrick (Pleasantville, NY) VR1-NIC Variable Angle Reflection Accessory mounted with a Harrick PWG-U1R Wire-Grid Polarizer for obtaining the p-polarization. The modulation frequency of FT-IR was 60 kHz, and the IR ray was detected by a liquid-N2 cooled MCT detector.…”
Section: Ir Er Measurementsmentioning
confidence: 99%
“…IR ER measurements 8,9,12 were performed on a Thermo Fischer Scientific (Madison, WI) Magna550 FT-IR spectrometer equipped with a Harrick (Pleasantville, NY) VR1-NIC Variable Angle Reflection Accessory mounted with a Harrick PWG-U1R Wire-Grid Polarizer for obtaining the p-polarization. The modulation frequency of FT-IR was 60 kHz, and the IR ray was detected by a liquid-N2 cooled MCT detector.…”
Section: Ir Er Measurementsmentioning
confidence: 99%
“…This tilt angle suggested that the structure of the contaminant was in a completely disordered state [28]. Figure 5 shows the IP mode spectra of the quartz substrate after each treatment.…”
Section: Resultsmentioning
confidence: 98%
“…Since the band locations of the νs(CH2) and νa(CH2) modes are 2850 and 2917 cm -1 , respectively, which indicate that the hydrocarbon chain has the trans-zigzag conformation, 12 Eq. (2) must hold.…”
Section: Resultsmentioning
confidence: 99%
“…When a molecule of metallic stearate is involved in an ordered monolayer, the νa(CH3) mode is known to split into the inskeleton and out-of-skeleton modes. 12,26 In this situation, the two modes would give different components on the IP and OP spectra, which depend on the molecular tilt angle. Therefore, there is always a band shift between the band locations of the νa(CH3) mode in the two spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation